"I'd make thee eat the mischief thou hast vented": Discourse of Law in Ben Jonson's Catiline His Conspiracy. Issue 1 (May 2017) - Shimizu, Akihiko
Abstract : This essay explores the discourse of law that constitutes the controversial apprehension of Cicero's issuing of the ultimate decree of the Senate ( senatus consultum ultimum ) in Catiline . The play juxtaposes the struggle of Cicero, whose moral character and legitimacy are at stake in regards to the extra-legal uses of espionage, with the supposedly mischievous Catilinarians who appear to observe legal procedures more carefully throughout their plot. To mitigate this ambivalence, the play defends Cicero's actions by depicting the way in which Cicero establishes the rhetoric of public counsel to convince the citizens of his legitimacy in his unprecedented dealing with Catiline. To understand the contemporaneousness of Catiline, I will explore the way the play integrates the early modern discourses of counsel and the legal maxim of 'better to suffer an inconvenience than mischief, ' suggesting Jonson's subtle sensibility towards King James's legal reformation which aimed to establish and deploy monarchical authority in the state of emergency (such as the Gunpowder Plot of 1605). The play's climactic trial scene highlights the display of the collected evidence, such as hand-written letters and the testimonies obtained through Cicero's spies, the Allbroges, as proof of Catiline's mischievous character. I argue that the tactical negotiating skills of the virtuous and vicious characters rely heavily on the effective use of rhetoric exemplified by both the political discourse of classical Rome and the legal discourse of Tudor and Jacobean England.